Effects of camel hump fat, palm olein oil, and corn oil feed additives on plasma lipids and adipose tissues in rats - Alshaikhsaleh, Shaheed Mohammed; Saleh, Farag Ali; Al-Otaibi, Mutlag Mohammed (Frontiers in Nutrition, 2025)
Hyperlipidemia is an important risk factor for cardiovascular disease and a leading cause of mortality and is often associated with obesity. Different types of fats and oils may have different effects on cardiovascular disease and obesity. This study investigated the effects of palm olein oil (PO), corn oil (CO), and camel hump fat (CHF) on plasma lipids and white adipose tissues of rats. A total of 18 male albino rats were divided equally into three groups. Each group was fed a diet containing one of these types of oils and fats for 8 weeks. The levels of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total triglyceride (TG), glucose, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were analyzed in blood plasma. Body mass index (BMI), body weight gain (%BWG), and the weight of adipose tissues were investigated. The results showed no significant differences between groups in TC. However, the highest level of HDL-C was observed in the CHF group, with no significant differences in the PO group and a significant decrease in the CO group. The CHF group showed a significant reduction in LDL-C, blood glucose levels, and the atherosclerosis index compared with the other groups. Furthermore, the lowest TG level was observed in the CHF group, with no significant difference compared with the CO group. The PO group showed a significant decrease in the ALT level compared with the other groups. The lowest AST level was observed in the PO group, with no significant difference compared with the CO group. A significant decrease in the percentage of total adipose tissues, namely epididymal, retroperitoneal, and perirenal cells, was observed in the CHF group. In conclusion, CHF consumption may have a positive effect on plasma lipids and obesity. Moreover, we recommend the completion of research to identify the optimal combination of vegetable oils and CHF for achieving a balance among the health indicators included in this study.